Success for Big Infectious Disease Reimbursement Policy in China - Kun-xi Nie; Chan Wang (Journal of Public Health International, 2019)
Big infectious diseases do harm to the whole society and it is highly crucial to control them on time. China has successful experience of launching reimbursement policy to control big infectious diseases, Severe Acute Respiratory Syndromes (SARS), efficiently. By evolution model, this article illustrates the efficiency of big infectious disease reimbursement policy in China. On one hand, the number of infected persons decreases under big infectious disease reimbursement policy in China. On the other hand, the total expenditures to cure also under control. In summary, big infectious disease reimbursement policy in China can support as an efficient example to cope with big infectious diseases.
Keywords: reimbursement policy